Determination of Bending and Axial Compression Youngâ€™s Modulus of Cellular Mortar Exposed to High Temperatures - A. Othuman Mydin, M; Mohamad, N; Johari, I; A. Abdul Samad, A (International Journal of Engineering and Technology, 2018)
This paper focuses on laboratory investigation to scrutinize and portray the Youngâ€™s modulus of cellular mortar exposed to high temperatures. Two densities of cellular mortar of 600 and 900 kg/m3 density were cast and tested under axial compression and 3-point bending. The tests were performed at room temperature, 105Â°C, 205Â°C, 305Â°C, 405Â°C, 505Â°C, and 605Â°C. The results of this study consistently indicated that the loss in toughness for cement based material like cellular mortar exposed to high temperatures happens principally after 105Â°C, irrespective of density of cellular mortar. This specifies that the principal contrivance instigating stiffness deprivation is micro cracking in the cement matrix, which happens as water magnifies and disappears from the porous body. As projected, decreasing the density of cellular mortar diminishes its compressive strength and bending strength. Though, for cellular mortar of different densities, the normalized strength-temperature and Youngâ€™s modulus-temperature relationships are comparable.Â Â